Islamisation Theories of Malay Culture: Issues and Responses - Muhamad Sayuti Mansor; Mohammed Farid Ali Al-Fijawi (Universitas Islam Negeri Sunan Kalijaga, 2021)
Interaction between Islamic teachings and cultures has resulted in the Islamisation of culture. The Malay culture was not an exception as Islam has transformed it into a Malay-Islamic culture. But it has raised questions on how Islamic teachings interacted with the indigenous culture before Islamising it and the degree of success of this process. These questions later on turned into a heated polemic, dividing the scholars into those who support the Islamisation of culture and those who oppose it. This study will look into the Islamisation theories of Malay culture deliberated by the orientalists and comparing them to the responses from contemporary Muslim scholars. It will be argued that both of these camps have opposing views regarding the basis of philosophical, sociological and historical theories in the Islamisation of culture. While the orientalist camp condemned it, Muslim scholars see it as a remarkable process in transforming the human culture.